2014
DOI: 10.35188/unu-wider/2014/844-5
|View full text |Cite
|
Sign up to set email alerts
|

Did rapid smallholder-led agricultural growth fail to reduce rural poverty? Making sense of Malawi’s poverty puzzle

Abstract: Typescript prepared by Jenny Stanley Smith for UNU-WIDER. UNU-WIDER gratefully acknowledges the financial contributions to the research programme from the governments of Denmark, Finland, Sweden, and the United Kingdom. The World Institute for Development Economics Research (WIDER) was established by the United Nations University (UNU) as its first research and training centre and started work in Helsinki, Finland in 1985. The Institute undertakes applied research and policy analysis on structural changes affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…Malawi is a small landlocked country in Sub‐Saharan Africa that is dominated by agriculture with an employment share of 80% and contributing a third to GDP. Despite economic growth averaging around 5% per annum for the past 10 years, Malawi remains one of the poorest countries in the world with a GDP per capita of 471 USD in 2010 and about half of the population still living below the national poverty line (Pauw et al., ; World Bank, ). This is because its population of around 15 million people in 2010 is one of the fastest growing in Sub‐Saharan Africa with a stable growth rate of about 3% per annum, quickly eating up any gain in total GDP.…”
Section: Agriculture and Irrigation In Malawimentioning
confidence: 99%
“…Malawi is a small landlocked country in Sub‐Saharan Africa that is dominated by agriculture with an employment share of 80% and contributing a third to GDP. Despite economic growth averaging around 5% per annum for the past 10 years, Malawi remains one of the poorest countries in the world with a GDP per capita of 471 USD in 2010 and about half of the population still living below the national poverty line (Pauw et al., ; World Bank, ). This is because its population of around 15 million people in 2010 is one of the fastest growing in Sub‐Saharan Africa with a stable growth rate of about 3% per annum, quickly eating up any gain in total GDP.…”
Section: Agriculture and Irrigation In Malawimentioning
confidence: 99%
“…In contrast, semi-elasiticities reported in the final column are strictly rooted in level changes in the poverty rate. Stifel and Woldehanna (2016), and Pauw et al (2016) in deriving utility consistent consumption poverty lines. Poverty rates are reported in two time periods based on the associated food poverty lines and 125 per cent poverty lines.…”
Section: Elasticities Poverty-growth Elasticities and Semi-elasticimentioning
confidence: 99%
“…They claimed that basic problems such as illegal markets for coupons and fertilizers, leakage of coupons, failure to establish a system of beneficiary and targeting are a serious problem which makes the program ineffective. In line to this, Pauw et al (2016) used constructed regional poverty lines for Malawi and found that the program did not benefit those close enough to the poverty line to be lifted out of poverty. In addition, Mvula et al (2011) in their qualitative evaluation of the 2010/11 farm input subsidy program also found that there were several growing challenges which hinder the FISP from reaching out to most vulnerable poor targeted beneficiaries.…”
Section: Literature Reviewmentioning
confidence: 99%